Analysis on Chemical Composition of Urinary Calculi and Evaluation on Metabolic Disturbance in 1080 Uyghur, Kazakh and Han Nationality Patients of Xinjiang: Analysis of Urinary Calculi and Metabolic Disturbance - Farooqi, Muhammad Rizwan; Tusong, Hamulati; Aji, Kaisaier; Yu Jie, Wang (Pakistan Journal of Health Sciences, 2023)
Urinary stones pose a significant health concern globally. The incidence rates vary and are influenced by diverse factors. Despite advancements in the treatment modalities, increasing rate of urinary stones necessitates the development of stone prevention strategies and understanding of metabolic risk factors. Objective: To determine the relationship between chemical composition of urinary calculi and evaluation on metabolic disturbance in 1080 Uyghur, Kazakh and Han patients of Xinjiang. Methods: The stone composition of 1080 patients and analysis of 24-h urine and serum biochemistry results of 775 cases was evaluated by infrared spectroscopic analysis and automatic biochemical machine respectively. Results: Among 644 cases of urinary stones, calcium oxalate stones (409 cases) and mixed type stones (436 cases) were predominant. Metabolic disturbances were found in 643 cases (82.97%) out of 775 patients, showing various urinary abnormalities like hyperuricosuria, hyperoxaluria, hyper-phosphaturia, hyper-cystinuria, hypercalciuria, hypomagnesuria, hypocitraturia, and reduced urine volume (<2000ml in 407 cases). Conclusions: Urinary calculi have intimate connection with metabolic evaluation. Metabolic evaluation and composition of urinary calculi have great significance in treatment and prevention of urinary calculi.